2020
DOI: 10.1590/s0004-2803.202000000-24
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Pattern of Symptoms in Colorectal Cancer Patients

Abstract: BACKGROUND: Colorectal cancer is the third most common type of cancer in the world and the increased survival of the colorectal cancer population is very significant. Thus, it becomes relevant to study the symptoms associated with the progression of the disease and treatment, for proper clinical management. OBJECTIVE: To describe the clinical and epidemiological profile of colorectal cancer patients and to identify the most prevalent signs and symptoms patterns. METHODS: Cross-sectional study evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
8
3
4
Order By: Relevance
“…O CCR se inicia como um tumor em desenvolvimento na parede interna do cólon ou do reto, onde as células dessa região acumulam alterações epigenéticas de manifestação lenta e gradual, com tempo de desenvolvimento entre 10 a 20 anos. A sintomatologia pode variar de acordo com a faixa etária, com emagrecimento, dor, disfunção no trato urinário, úlceras orais e ansiedade (ARAN et al, 2016;MELLO et al, 2020;TESTA;PELOSI;CASTELLI, 2018).…”
Section: Objectiveunclassified
“…O CCR se inicia como um tumor em desenvolvimento na parede interna do cólon ou do reto, onde as células dessa região acumulam alterações epigenéticas de manifestação lenta e gradual, com tempo de desenvolvimento entre 10 a 20 anos. A sintomatologia pode variar de acordo com a faixa etária, com emagrecimento, dor, disfunção no trato urinário, úlceras orais e ansiedade (ARAN et al, 2016;MELLO et al, 2020;TESTA;PELOSI;CASTELLI, 2018).…”
Section: Objectiveunclassified
“…O câncer colorretal é provocado devido ao acúmulo de mutações no material genético geradas ao decorrer da vida, sendo que existem muitas evidências científicas que apontam para a dieta, bem como a ausência da prática de exercícios físicos, como fatores relacionados com o desenvolvimento deste tipo de câncer (MELLO et al, 2020). Além disso, segundo Fiore e colaboradores (2013, p. 583), "a progressão do CCR está associada com fatores genéticos, como por exemplo, a ausência dos genes supressores tumorais e de mecanismos de reparo do genoma, bem como a ativação de oncogenes".…”
Section: )unclassified
“…Symptoms such as gastrointestinal dysfunction, fatigue, and peripheral neuropathy were commonly reported, and anxiety, depression, and other adverse emotions increase stress and severity of the symptoms. Moreover, many studies [ 4 , 5 ] have shown that anxiety and depression are closely related to the symptoms, and long-term negative emotions directly affect sleep quality. These problems will directly or indirectly affect the treatment and prognosis of patients with CRC [ 6 ] and lead to a reduction in quality of life, eventually increasing the risk of suicide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%